2016
DOI: 10.1016/j.indmarman.2016.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Usability perspective on social media sites' adoption in the B2B context

Abstract: While social media sites have been successfully adopted and used in the B2C context, they are perceived to be irrelevant in B2B marketing. This is due to marketers’ perception of poor usability of these sites in the B2B sector. This study investigates the usability of social media sites when adopted for B2B marketing purposes in the one of world’s largest social media market: China. Specifically, by extending the Technology Acceptance Model with Nielsen’s Model of Attributes of System Acceptability, we assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
153
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(169 citation statements)
references
References 53 publications
11
153
3
2
Order By: Relevance
“…For City Skylight social media tools have proven to be effective in gaging interest and converting this into actual business opportunities. This finding contradicts a study undertaken by Lacka and Chong (2016), who found that social media tools are considered irrelevant in a B2B context, as they are too time consuming. However, as the research was conducted with B2B professionals of large organisations, it could be suggested that there is a difference between large and micro-sized organisations.…”
Section: A5 Leafletcontrasting
confidence: 90%
“…For City Skylight social media tools have proven to be effective in gaging interest and converting this into actual business opportunities. This finding contradicts a study undertaken by Lacka and Chong (2016), who found that social media tools are considered irrelevant in a B2B context, as they are too time consuming. However, as the research was conducted with B2B professionals of large organisations, it could be suggested that there is a difference between large and micro-sized organisations.…”
Section: A5 Leafletcontrasting
confidence: 90%
“…New communication tools have become a major issue within society and have captured the attention of researchers around the world as a significant research topic (Park & Kim, 2013). SNSs have led to the publication of a number of studies in different contexts such as the stock market, parliamentary and presidential elections, emergency events, crises, health, education, business, and so on (Evangelopoulos, Magro, & Sidorova, 2012;Lacka & Chong, 2015;Liu, Liu, & Li, 2012;Pere-Latre, Portilla, & Blanco, 2010;Prybutok, 2013). Owing to the differences in SNSs' pur-…”
Section: Introductionmentioning
confidence: 99%
“…There are eight concepts included in their model and these are error prevention, information needs, memorability, learnability, competency, performance speed, flexibility/customization, and other outcomes. Another study [31] investigated the usability on social media sites' when adopted for business-to-business (B2B) marketing purposes in China. The authors' investigation found that three factors such as learnability, efficiency, and memorability impact the perceived usability.…”
Section: Related Workmentioning
confidence: 99%